Fungal Infection Exacerbate Nasal Polyposis: A study conducted at KGN Teaching Hospital Bannu-KPK. - Mohammad Iqbal; Khan, Sahibzada Fawad; Khan, Sohail; Ahmad, Wasim (International Journal of Endorsing Health Science Research, 2021)
Background: Nasal polyps were believed to be small tumours of nasal or sinus mucosa. With progressing research, they are associated with enlargement or swelling of nasal or sinus mucosa, allergy, asthma, any infection, sensitivity to aspirin, and/or cystic fibrosis unclear etiology. The present study aims to evaluate the prevalence of fungal infections that can result in the onset of nasal polyposis in the residents of district Bannu, Pakistan. Methodology: A cross-sectional study was conducted at the ENT Department of Khalifa Gul Nawaz (KGN) teaching hospital in Bannu from March 2018 to February 2020, including 180 polyposis patients with the presence or absence of any fungal infestation. The subjects possessing mass other than nasal polyp based on clinical diagnosis were excluded from the study. The fungal infestation was observed with nasal endoscopy, and the patients were hospitalized for functional endoscopic sinus surgery (FESS). The staging of the nasal polyposis was based on the CT scan findings. The condition was classified into three grades, i.e., grade I, II and III. The data was statistically analysed on SPSS version 20.0. Results: Out of 180 patients diagnosed clinically for nasal polyposis, 97(53.88%) were males. The fungal infestation was positive in 73(41%) specimens. Around 52.72% of patients were found with bilateral involvement. Of which, 31.57% were diagnosed with an allergic event. The fungus Aspergillus was observed in 40.55% of specimens. The one-year follow-up displayed an overall recurrence rate of 40%, i.e., 38(52.05%) patients from the fungal group and 34(47.22%) from the non-fungal group. Conclusion: It is concluded from the study outcomes that the incidence of nasal polyposis with or without fungal infection is associated with the environment and the discrete host response. Moreover, individuals living with lower socioeconomic conditions in crowded and humid areas tend to suffer more.